Implementation of a Gamification Platform in a Master Degree (Master in Economics) - Juan Carlos Fernández-Zamora; Daniel Arias-Aranda (WPOM : Working Papers on Operations Management)
Nowadays, educational platforms focus on offering content as well as covering the main needs of users. However, very few or almost none offers anything to improve the integration between users and the system. It is intended to use the thinking of games and the mechanics of games to solve these problems and motivate users. An experiment has been carried out for this reason, in which an educational platform, created in a personalized way for the students of the Master in Economics of the University of Granada, becomes the day to day of these students, yielding results and Statistics on how to improve student motivation.